The effects of six months Persicaria minor extract supplement among older adults with mild cognitive impairment: a double-blinded, randomized, and placebo-controlled trial - Huijin Lau; Suzana Shahar; Mazlyfarina Mohamad; Nor Fadilah Rajab; Hanis Mastura Yahya; Normah Che Din; Hamzaini Abdul Hamid (BMC, 2020)
Abstract Background Persicaria minor extract exhibits antioxidant and anti-inflammatory properties and has potential effects on cognitive function and mood. However, the effects of P.minor on brain activation and biomarkers have not been studied among older adults. This multicentre, randomized, double-blinded, placebo-controlled study aimed to investigate the effect of 6 months P.minor extract supplement (Biokesum®) on cognition, mood, biomarkers, and brain activation among older adults with Mild Cognitive Impairment (MCI). Method A total of 36 Malaysian community-dwelling older adults with MCI (60-75-year-old) were randomized into Biokesum® (n = 18) and placebo group (n = 18). Each subject consumed one capsule of Biokesum® (250 mg/capsule) or placebo (maltodextrin, 280 mg/capsule) twice daily for 6 months. Cognitive function and mood were assessed at baseline, 3rd, and 6th-month using neuropsychological tests (MMSE, Digit Span, RAVLT, Digit Symbol, and Visual Reproduction) and Profile of Mood State (POMS) questionnaire. Blood lipid profile, fasting blood glucose, and biomarkers (MDA, LPO, COX-2, iNOS, and BDNF) were measured at baseline and 6th month. By the end of the intervention, there were 30 compliers (Biokesum®: N = 15; Placebo: N = 15) and 6 dropouts. For brain activation assessment, 15 subsamples (Biokesum®: N = 8; Placebo: N = 7) completed N-back and Stroop tasks during fMRI scanning at baseline and 6th month. The dorsolateral prefrontal cortex (Brodmann's area 9 and 46) was identified as a region of interest (ROI) for brain activation analysis using SPM software. Results Two-way mixed ANOVA analysis showed significant improvements in Visual Reproduction II (p = 0.012, partial η2 = 0.470), tension (p = 0.042, partial η2 = 0.147), anger (p = 0.010, partial η2 = 0.207), confusion (p = 0.041, partial η2 = 0.148), total negative subscales (p = 0.043, partial η2 = 0.145), BDNF (p = 0.020, partial η2 = 0.179) and triglyceride (p = 0.029, partial η2 = 0.237) following 6 months of Biokesum® supplementation. Preliminary finding also demonstrated significant improvement at 0-back task-induced right DLPFC activation (p = 0.028, partial η2 = 0.652) among subsamples in Biokesum® group. No adverse events were reported at the end of the study. Conclusion Six months Biokesum® supplementation potentially improved visual memory, negative mood, BDNF, and triglyceride levels among older adults with MCI. Significant findings on brain activation at the right DPLFC must be considered as preliminary. Trial registration Retrospectively registered on 30th August 2019 [ ISRC TN12417552 ].